Hypoxia-dependent expression of ADAM8 in human pancreatic cancer cell lines - Valkovskaya, N.V. (Experimental Oncology, 2008)
One of the most characteristic features of malignant tissue is the high level of intratumoral hypoxia, which is considered as a powerful factor for induction of tumor aggressiveness and malignant progression. Pancreatic cancer (PC) is a near fatal disease with very unfavorable clinical outcome despite the application of different treatment regimes. It was shown that PC is characterized by high level of hypoxia. Aim: To clarify the correlation between tumor hypoxia and ADAM8 protein expression. Materials and Methods: ASPC-1, Panc-1, BxPC-3, Capan-1, MiaPaCa-2, Colo-357, Su8686 and T3M4 cell lines were used in the study. Expression of mRNA ADAM8 was evaluated by real-time quantitative polymerase chain reaction method. Immunoblot analysis was used to evaluate the expression of ADAM8 protein. Results: Hypoxia induced a 2.5–5.9-fold increase of ADAM8 mRNA levels of in the examined pancreatic cancer cell lines except Panc-1 (p = 0.046). On the protein level, hypoxia induced a 1.2–5.9-fold increase of the ADAM8 prodomain removal form (90 kDa) in 5/8 pancreatic cancer cells. Moreover, hypoxia induced a 1.3–2.0-fold increase of the remnant form ADAM8 (60 kDa) in 4/8 pancreatic cancer cell lines: Aspc-1, Colo-357, Panc-1, T3M4. Conclusion: It was observed the clear tendency in the increase both of ADAM8 mRNA and ADAM8 protein levels in pancreatic cancer cell lines under hypoxia compared to normal conditions of oxygenation. A potential role of ADAM8 as a hypoxia-dependent protein in the pathogenesis and evolution of pancreatic cancer that is characterized by high level of intratumoral hypoxia can be suggested. Введение: известно, что характерной чертой злокачественных опухолей является внутриопухолевая гипоксия, положительно
влияющая на злокачественную прогрессию. Рак поджелудочной железы (РПЖ) является очень агрессивной опухолью,
обладающей высокой способностью к инвазии в близлежащие ткани и органы, что обусловливает неудовлетворительные
результаты лечения. Показано при этом, что РПЖ относится к новообразованиям с высокой степенью гипоксии. Цель:
установление возможной зависимости экспрессии белка АДАМ8 и его мРНК от уровня оксигенации клеток. Материалы
и методы: использовали клеточные линии РПЖ человека. Экспрессию мРНК и белка ADAM8 определяли методами qRTPCR
и вестерн-блот-анализа соответственно. Результаты: установлено, что гипоксия индуцировала повышение уровня
мРНК АDAM8 в 2,5–5,9 раза в исследованных клеточных линиях РПЖ, за исключением клеток линии Panc-1. В клетках
линий BxPC-3, Capan-1 и Su8686 выявлено наиболее значительное возрастание уровня экспрессии мРНК ADAM8 при
гипоксии (p = 0,046). С помощью вестерн-блот-анализа показано, что экспрессия удаляемой формы продомена ADAM8
(90 kDa) усиливалась в несколько раз при гипоксии в 5 из 8 изученных клеточных линий РПЖ. Гипоксия индуцировала
повышение экспрессии остаточной формы ADAM8 (60 kDa) в 4 из 8 клеточных линий РПЖ: Aspc-1, Colo-357, Panc-1,
T3M4, хотя изменения оказались умеренно выраженными. Выводы: в клеточных линиях РПЖ человека отмечается четкая
тенденция к повышению при гипоксии уровня экспрессии, как мРНК, так и белка ADAM8, что позволяет предположить
зависимость экспрессии от уровня оксигенации и потенциальную роль ADAM8 в развитии и прогрессии РПЖ, который
отличается высокой степенью внутриопухолевой гипоксии.